Institutionalization process of service innovation: Overcoming competing institutional logics in service ecosystems - Elina Jaakkola; Leena Aarikka-Stenroos; Paavo Ritala (Springer, 2022)
Service science is concerned with the question of how systems can co-create value in an optimal way. In essence, innovations aim at enabling better value co-creation; but at the same time, cause disruption and tensions in the service ecosystem by challenging prevailing practices. This chapter examines the development and diffusion of a broad scale heath care service innovation – the Electronic Prescription system (eRX) – as a process of institutionalization within a service ecosystem. This case represents an innovation process that attempts to solve a major societal challenge, rationalization of medication and reduction of medication errors and abuse. This change requires commitment and adaptation by diverse actors in multiple service systems affected by the eRX, but is nearly disabled by these actors’ competing and even conflicting institutional logics. We examine how diverse stakeholders slowly move towards a convergent institutional logic as the innovation is gradually institutionalized in the broader service ecosystem, and discuss the major challenges along this process. This chapter highlights the dilemma of change in service ecosystems and highlights the role of institutions therein.
Handbook of Service Science, Volume 2